Elementos para pensar la formación pedagógica y didáctica de los profesores en la universidad1 - gonzález, hamlet; Malagónlez, Rusby (Colombian Applied Linguistics Journal, 2015)
University Teachers training is a key aspect when regarding the quality of education imparted to future professionals and when qualifying the contribution of human resource to society. Taking into account discussions of analysis suggested by local and foreign authors, this reflection paper proposes an analysis of teachers training at university level in Colombia and paths to contribute on its development. The main contributions to the debate are: a) establishing a unified policy of teachers training in Colombia is essential, despite the lack of political desire from government agencies; b) recovering the relevance of the pedagogical knowledge in order to improve teachers training by emphasizing on communicational aspects; c) finally, highlighting the importance of carrying out pedagogical and educational research projects which seldom take place.